2012
DOI: 10.1109/lpt.2011.2179642
|View full text |Cite
|
Sign up to set email alerts
|

A Data Rate- and Modulation Format-Independent Packet-Switched Optical Network Test-Bed

Abstract: Abstract-Adopting high data rates and advanced modulation formats in optical interconnection networks will enable future computing systems to achieve greater performance and scalability. We experimentally demonstrate the data rate and modulation format independence of a 4 × 4 optical packetswitched network test-bed. Leveraging wavelength-division multiplexing, we show the transmission of multiwavelength 320-Gb/s optical packets, using 8 × 40-Gb/s wavelength-striped payloads. Both on-off keying (OOK) and differ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
2
0

Year Published

2012
2012
2015
2015

Publication Types

Select...
3
1

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 7 publications
1
2
0
Order By: Relevance
“…Due to carrier density variations, saturation effects, and inter-channel nonlinear effects in the SOA, the multi-wavelength packets suffer from significant waveform distortion under switching. As a result, the power penalties measured in this experiment are higher than those observed in [19]. The observed power penalty (BER at ) for twenty-five wavelengths is also recorded in Fig.…”
Section: B 4 4 Photonic Switching Node Implemented On a Modular Optisupporting
confidence: 47%
See 1 more Smart Citation
“…Due to carrier density variations, saturation effects, and inter-channel nonlinear effects in the SOA, the multi-wavelength packets suffer from significant waveform distortion under switching. As a result, the power penalties measured in this experiment are higher than those observed in [19]. The observed power penalty (BER at ) for twenty-five wavelengths is also recorded in Fig.…”
Section: B 4 4 Photonic Switching Node Implemented On a Modular Optisupporting
confidence: 47%
“…Unfortunately, as a result of the complicated modulation and demodulation schemes, the limited durability of the required devices precludes the use of such a system in large-scale computing environments. The authors of [19] have experimentally demonstrated packet switching using both 8 40-Gb/s on-off keying (OOK) and differential-phase-shiftkeying (DPSK) through an optical network testbed. However, the 4 4 switch architecture used suffers from internal blocking, limiting its effective switching capacity.…”
Section: B 4 4 Photonic Switching Node Implemented On a Modular Optimentioning
confidence: 99%
“…The FPGA contains the routing control logic, which allows the network to be reconfigured to realize diverse network topologies. The SOAs act as optical on/off gates, configured in a broadcast-and-select manner, to enable nanosecond switching of broadband, high data-rate messages [28].…”
Section: Optical Network Test-bedmentioning
confidence: 99%